Ride Hailing Regulations in Cali, Colombia: Towards Autonomous and Decent Work - Reilly, Katherine M. A.; Lozano-Paredes, Luis H. (Information and Communication Technologies for Development. Strengthening Southern-Driven Cooperation As a Catalyst for ICT4D, 2019)
In this article we explore the decent work standard developed by Richard Heeks for digital online labour markets and use a review of empirical research about ride-hailing to adapt this framework to the location-based service delivery market. The framework is then tested against an in-depth analysis of informality and precarity in the ride hailing sector in Cali, Colombia. Findings show that location-based platform workers in Cali lack many decent work protections. However, the case study also demonstrates that workers are evolving creative ways to grapple with specific aspects of precarity within the ride-hailing sector. Based on this analysis, we argue that policy analysis and worker innovations need to ‘meet in the middle’ rather than follow policy recommendations emanating from other jurisdictions. We suggest some specific policy reforms that will be appropriate to the Colombian and Latin American context.